High-Quality Genome Resource of Eight Strains of Ralstonia pseudosolanacearum Causing Bacterial Wilt in Madagascar - Marie Veronique Nomenjanahary; Hasina Rasoamanana; Stéphanie Javegny; Adrien Rieux; Santatra Ravelomanantsoa; Stéphane Poussier; Yann Pecrix (PhytoFrontiers)
The Ralstonia solanacearum species complex (RSSC) is a significant pathogen that causes bacterial wilt, affecting numerous plant species and posing a critical threat to food security in tropical and subtropical regions. In recent years, multiple bacterial wilt outbreaks have been reported in Madagascar, and the phylogenetic assignment of the collected strains revealed a high prevalence of phylotype I, belonging to the species Ralstonia pseudosolanacearum. This study presents the first genomic sequences of eight Malagasy phylotype I strains, collected from diverse regions and host plants, representing the phylogenetic diversity and varying levels of prevalence in the field. Genomic analysis, including phylogenetic positioning, revealed that Malagasy strains share evolutionary links with strains from different continents, whereas some formed unique monophyletic groups. Type III effector repertoires, key virulence factors, were analyzed, identifying core and lineage-specific effectors. These genomic data provide essential resources for future studies on host adaptation and the molecular mechanisms driving the epidemic success of the RSSC in Madagascar. [Figure: see text] Copyright © 2025 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.